The marine triterpene glycoside frondoside A induces p53-independent apoptosis and inhibits autophagy in urothelial carcinoma cells. Issue 1 (December 2017) - Dyshlovoy, Sergey; Madanchi, Ramin; Hauschild, Jessica; Otte, Katharina; Alsdorf, Winfried; Schumacher, Udo; Kalinin, Vladimir; Silchenko, Alexandra; Avilov, Sergey; Honecker, Friedemann; Stonik, Valentin; Bokemeyer, Carsten; et al.
Abstract Background Advanced urothelial carcinomas represent a considerable clinical challenge as they are difficult to treat. Platinum-based combination regimens obtain response rates ranging from 40 to 70% in first-line therapy of advanced urothelial carcinoma. In the majority of cases, however, the duration of these responses is limited, and when progression occurs, the outcome is generally poor. Therefore, novel therapeutic strategies are urgently needed. The purpose of the current research is to investigate the anticancer effects and the mode of action of the marine triterpene glycoside frondoside A in p53-wild type and p53-deficient human urothelial carcinoma cells. Methods Activity of frondoside A was examined in the human urothelial carcinoma cell lines RT112, RT4, HT-1197, TCC-SUP, T-24, and 486p. Effects of frondoside A on cell viability, either alone or in combination with standard cytotoxic agents were investigated, and synergistic effects were analyzed. Pro-apoptotic activity was assessed by Western blotting and FACS, alone and in combination with a caspases-inhibitor. The impact of functional p53 was investigated by siRNA gene silencing and the p53 inhibitor pifithrin-α. Effects on autophagy were studied using LC3B-I/II and SQSTM/p62 as markers. The unpaired Student'st -test was used for comparison of the data sets. Results Frondoside A shows high cytotoxicity in urothelial carcinoma cells with IC50s ranging from 0.55 to 2.33 μM while higher concentrations of cisplatin are required for comparable effects (IC50  = 2.03 ~ 5.88 μM). Induction of apoptosis by frondoside A was associated with the regulation of several pro-apoptotic factors, like caspase-3, -8, and -9, PARP, Bax, p21, DNA fragmentation, and externalization of phosphatidylserine. Remarkably, inhibition of p53 by gene silencing or pifithrin-α pretreatment, as well as caspase inhibition, did not suppress apoptotic activity of frondoside A, while cisplatin activity, in contrast, was significantly decreased. Frondoside A inhibited pro-survival autophagy, a known mechanism of drug resistance in urothelial carcinoma and showed synergistic activity with cisplatin and gemcitabine. Conclusions A unique combination of properties makes marine compound frondoside A a promising candidate for the treatment of human urothelial carcinomas.